2009
DOI: 10.1007/s00216-009-3228-4
|View full text |Cite
|
Sign up to set email alerts
|

Separation of peptides by HPLC using a surface-confined ionic liquid stationary phase

Abstract: A butylimidazolium bromide surface-confined ionic liquid stationary phase was synthesized in-house. The synthesized phase was investigated for the separation of five peptides (Gly-Tyr, Val-Tyr-Val, leucine enkephalin, methionine enkephalin, and angiotensin-II). The peptides were successfully separated in less than 5 min. The effect of trifluoroacetic acid (TFA) on the separation of peptides was evaluated with results confirming that TFA was not acting as ion-pairing agent in separation of peptides on this phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…[20][21][22] Compared with chemical modification of reactive groups, post grafting of linear polymer chains can provide much more functionalities and interaction sites, which benefits analyte retention and HPLC separation. Two general routes have been used to graft linear polymer chains onto the surface of solid supports known as "grafting to" and "grafting from" method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Compared with chemical modification of reactive groups, post grafting of linear polymer chains can provide much more functionalities and interaction sites, which benefits analyte retention and HPLC separation. Two general routes have been used to graft linear polymer chains onto the surface of solid supports known as "grafting to" and "grafting from" method.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ILs have been intro-duced to silica particle-packed HPLC column and successfully applied in reversed-phase and ion-exchange mixed-mode chromatography for separation of neutral aromatic molecules, [20] peptides [21] and inorganic anions. [22] Thus, combination of versatile properties of ILs and unique characteristic of polymer monolith is an active area of research. So far to our knowledge, functionalization of polymer monolith with ILs has been rarely reported [23] and might be a facile approach to afford polymer monolith with mixed-mode HPLC performance.…”
Section: Introductionmentioning
confidence: 99%
“…This is an interesting finding, as it points out a complementary pathway to modify the SCIL SP besides changing substituents of the cation. Their subsequent study on the butylimidazolium-based phase (Sil-C 8 ImC 4 -Br) demonstrated that the SCIL SPs were promising for multi-modal separation [77]. This multi-modal character was validated by separation of five peptides (Gly-Tyr, Val-Tye, leucine enkephalin, methionine enkephalin and angiotensin-II).…”
Section: Reversed-phase Modementioning
confidence: 97%
“…Another feature of ILs is the inherent amphiphilicity of cation, so that they may be considered as short-chain cationic surfactants [30]. Therefore, the controllable structure property and amphiphilicity of ILs play an important role in separation, such as they have been used either as a functional group fixed on stationary phase of HPLC [31] or as running buffer additives in capillary electrophoresis [32][33][34][35][36] and microchip [28,37] for peptides or proteins separation.…”
Section: Introductionmentioning
confidence: 99%